Vertical wind profile distribution within canopy layer based on representative geometry model using wind tunnel experiment - S. A. Zaki; Y. M. H’ng; A. F. Mohammad; Jorge Alfredo Ardila‑Rey; Noor Alam; Mardiana Idayu Ahmad (Scientific Reports)
Abstract This study examined the mean and turbulent wind speed distribution within the canopy height of a tropical urban campus based on a representative geometry model via wind tunnel experiments. The vertical wind profiles were analysed around two high-rise buildings, Menara Razak (MR) and Residensi Tower (RT) at both wind directions (22.5° and 202.5°). To examine the influence of high-rise buildings on strong wind, the collected data of mean wind speed (u), root mean square (u rms ), and skewness (SK) were analysed. Effects of the wind direction, building layout or arrangement and building geometry under the canopy height were also examined. The results show that the building layout influenced the wind distribution within the target site, and the approaching wind flow direction also influenced the wind flow interaction with the building. The height of the target building (H) influenced the distance traveled by the vortices in the wake flow. For the MR and RT cases, the vortices could be affected up to a minimum distance of H and 1.5H, respectively. The study demonstrates that the building layout significantly influences the distribution of wind speeds within the canopy height of a tropical urban campus.